WORKSHOP PENYUSUNAN RPP DIFERENSIASI DAN MODUL PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DI SDN SELAKOPI KAB.BANDUNG BARAT - Agus Mulyanto; Rinrin Siti Maemunah; Uus Sopandi (LPPM Universitas Bina Bangsa, 2024)
This Community Service activity is a collaborative activity of three educational institutions, namely Universitas Islam Nusantara, SMKN 1 Cihampelas and SMPN 4 Cisompet.The purpose of this community service is to increase knowledge and skills and facilitate teachers in compiling Differentiated RPP and Pancasila Student Profile Strengthening Project modules. So as to minimize misconceptions related to differentiated learning and the Pancasila Student Profile Strengthening Project. This service was carried out at SDN Selakopi, West Bandung regency with the participants of one principal, eight teachers and one school operator. Service is carried out with four stages, namely preparation, implementation, evaluation and reflection. The implementation is carried out in the form of workshops and assistance in compiling differentiated RPP and modules of the Pancasila Student Profile Strengthening Project. Furthermore, the RRP that has been prepared is implemented in the classroom and class observations are carried out to determine the compatibility between the RPP made and the implementation in class. The results of this dedication show that the activity has been carried out and runs smoothly. The activity succeeded in correcting misconceptions related to differentiated learning and the Strengthening Pancasila Student Profile Project. With this activity, all participants can understand differentiated learning and the Pancasil Student Profile Strengthening Project. Furthermore, the teacher succeeded in compiling a differentiated lesson plan according to the subjects taught and the facilitator team of the Pancasila Student Profile Strengthening Project succeeded in compiling the Pancasila Student Profile Strengthening Project module. This activity not only focuses on workshop products but also on participants' understanding of differentiated learning and the Pancasila Student Profile Strengthening Project